Climate impacts on the ocean are making the Sustainable Development Goals a moving target travelling away from us. Issue 3 (12th June 2019) - Singh, Gerald G.; Hilmi, Nathalie; Bernhardt, Joey R.; Cisneros Montemayor, Andres M.; Cashion, Madeline; Ota, Yoshitaka; Acar, Sevil; Brown, Jason M.; Cottrell, Richard; Djoundourian, Salpie; González‐Espinosa, Pedro C.; Lam, Vicky; et al.
Abstract: Climate change is impacting marine ecosystems and their goods and services in diverse ways, which can directly hinder our ability to achieve the Sustainable Development Goals (SDGs), set out under the 2030 Agenda for Sustainable Development. Through expert elicitation and a literature review, we find that most climate change effects have a wide variety of negative consequences across marine ecosystem services, though most studies have highlighted impacts from warming and consequences of marine species. Climate change is expected to negatively influence marine ecosystem services through global stressors—such as ocean warming and acidification—but also by amplifying local and regional stressors such as freshwater runoff and pollution load. Experts indicated that all SDGs would be overwhelmingly negatively affected by these climate impacts on marine ecosystem services, with eliminating hunger being among the most directly negatively affected SDG. Despite these challenges, the SDGs aiming to transform our consumption and production practices and develop clean energy systems are found to be least affected by marine climate impacts. These findings represent a strategic point of entry for countries to achieve sustainable development, given that these two goals are relatively robust to climate impacts and that they are important pre‐requisite for other SDGs. Our results suggest that climate change impacts on marine ecosystems are set to make the SDGs a moving target travelling away from us. Effective and urgent action towards sustainable development, including mitigating and adapting to climate impacts on marine systems are important to achieve the SDGs, but the longer this action stalls the more distant these goals will become. A freePlain Language Summary can be found within the Supporting Information of this article. Abstract : A freePlain Language Summary can be found within the Supporting Information of this article.